Association of Gene Variations POMP, FLG, MTOR and ATG5 gene with the Risk of Asthma in Children - O.P. Volosovets; S.P. Kryvopustov; O.V. Pavlyk; O.V. Yemets; D.O. Stroi; V.Ye. Dosenko (Zaslavsky O.Yu., 2016)
The aim of this study was to determine the correlation between single-nucleotide polymorphisms in the proteasome maturation protein gene (POMP), filaggrin gene (FLG), mammalian target of rapamycin gene (MTOR) and autophagy gene (ATG5) and the development of asthma in children. Methods: clinical, genetic - determining the genotype of patients and healthy children using real-time polymerase chain reaction; statistical ones. Results. It was found that the distribution of genotypes in the studied groups was significantly different when analysing polymorphism in POMP gene: GG variant was detected in 9 healthy children and was absent in ill people, 32 patients and 37 healthy children had AG variant, 62 and 52 - allelic AA variant, while minor variant wasn't detected in patients with asthma at all (p < 0.05 by the χ2 criterion). Variants with the minor genotype of the FLG were found to be 2.5 times more frequent among patients than in control group: 5 patients and 2 healthy children had allelic variant AA, 27 and 36 - heterozygous variant GA, 67 and 61 - GG. Variants with minor genotype in MTOR gene were 2.4 times more often in the control group than in patients: 50 patients and 43 healthy children had major allelic variant TT, 36 patients and 32 healthy children had TC variant, 5 and 12 - CC variant. There was found a statistically significant difference in the distribution of genotypes of polymorphism in ATG5 gene: 51 patients and 43 healthy children were heterozygous (CT), 29 and 21 - had minor variant TT, 18 and 33 - major variant CC (p < 0.05 by the χ2). Minor polymorphism of ATG5 gene was associated with increased risk of early manifestation of the asthma (up to 3 years of life) (p < 0.05 by χ2). MDR-analysis has showed that polymorphism in ATG5 gene was the strongest predictor of asthma as it reduced entropy level by 7.88 %. Polymorphism in the POMP gene reduces entropy level by 5.21 %, polymorphism in the MTOR gene - by 1.18 %, polymorphism in the FLG gene - by 1.04 %. Conclusions. These polymorphisms may serve as prognostic markers for the development of asthma in children.